Mobilizing Vacuolar Sugar Increases Vegetative Triacylglycerol Accumulation - Anaokar, Sanket; Liu, Hui; Keereetaweep, Jantana; Zhai, Zhiyang; Shanklin, John (Frontiers in Plant Science, 2021)
Photosynthetically derived sugars provide carbon skeletons for metabolism and carbon signals that favor anabolism. The amount of sugar available for fatty acid (FA) and triacylglycerol (TAG) synthesis depends on sugar compartmentation, transport, and demands from competing pathways. We are exploring the influence of sugar partitioning between the vacuole and cytoplasm on FA synthesis in Arabidopsis by building on our previous finding that reduced leaf sugar export in the sucrose-proton symporter2 (suc2) mutant, in combination with impaired starch synthesis in the ADP-glucose pyrophosphorylase (adg1) mutant, accumulates higher sugar levels and increased total FA and TAG compared to the wild type parent. Here we sought to relocalize sugar from the vacuole to the cytoplasm to drive additional FA/TAG synthesis and growth. Arabidopsis suc2 adg1 was therefore crossed with tonoplast monosaccharide transporter mutants tmt1 and tmt2 and overexpression of the sucrose/proton cotransporter SUC4 in which tmt1 tmt2 impairs sugar transport to the vacuole from the cytoplasm and SUC4 overexpression enhances sugar transport in the reverse direction from the vacuole to the cytoplasm. A resulting homozygous suc2 adg1 tmt1 tmt2 SUC4 line was used to test the hypothesis that increased intracellular carbon supply in the form of sugars would increase both FA and TAG accumulation. The data shows that relative to suc2 adg1, suc2 adg1 tmt1 tmt2 SUC4 significantly increases leaf total FA content by 1.29-fold to 10.9% of dry weight and TAG by 2.4-fold to 2.88%, supporting the hypothesis that mobilizing vacuolar sugar is a valid strategy for increasing vegetative oil accumulation.